An example of the physical development program from an first division Croatian soccer league team with emphasis on sport science and load management - Matusinskij, M.; Krakan, I.; Novacic, V. (World Congress of Performance Analysis of Sport XII, 2018)
The main purpouse of this paper is to show an example of the physical development program from a First Division Croatian soccer league team with emphasis on sport science and load management with current limitations and potentional solutions. Throughout history there have been a lot of training systems and athlete development systems stated by the national sport organizations, but over the last 30 years, sport clubs have become a leaders in the development of system design to attain high performance in sport (Jukic et al., 2018). This paper shows an example of professional soccer team management in performance meaning, giving the readers insight what to focus on with emphasised approach to load management and sport science department. One of the motives of this paper was to draw attention to the responsible people that there is a way to adress the chanel of communication with other soccer clubs and with Croatian Football Federation. Using sRPE method and A:C ratios we can provide a deep insight at what state the player is before and after camp, tournament, championship. We can see that this is for now the best method for finding a solution for injury prevention and performance state of the players. There is a way.